OPOSISI PERSPEKTIF AL-QURAN - Muhammad Syarif Hasyim (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
Democracy in a country, even a slightest association, is a demand for their citizens. One of the most important instruments in democracy is openness is reflected in the criticisms, suggestions, or advice. It must be realized in order to attain the goals and ideals together. To achieve this goal, the opposition to run a function that is vital and important, as checks and balances, controls government supported by a majority. Opposition is not only defined as a challenger to government policy, but as part of the democratic system to provide feedback, suggestions, and advice to the government. Democracy and meaningful opposition cannot be opposed to Islam. In the texts of the Qur'an or the Hadith of the Prophet there are many indications and guidance about it even though the text / literal in the Qur'an cannot be found lafadz democracy and the opposition, but the substance of democracy and the opposition reflected in the obligation to carry out enjoining and forbidding the evil or advised each other and advised reminded of the truth in order to achieve khair ummah